2009
DOI: 10.1056/nejmoa0908629
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Platelet Blockade with Cangrelor during PCI

Abstract: The use of periprocedural cangrelor during PCI was not superior to placebo in reducing the primary end point. The prespecified secondary end points of stent thrombosis and death were lower in the cangrelor group, with no significant increase in the rate of transfusion. Further study of intravenous ADP blockade with cangrelor may be warranted. (ClinicalTrials.gov number, NCT00385138.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
337
0
14

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 570 publications
(356 citation statements)
references
References 25 publications
5
337
0
14
Order By: Relevance
“…This finding may be due in part to the more critical hemodynamic conditions of these patients that are associated, mainly in cardiogenic shock, with a significant reduction of the absorption of drugs from the intestine [27], in part to the difficulty to give them the needed antiplatelet therapy, mandatory after stent implantation. New intravenous antiplatelet drugs seem promising in reducing thrombotic events related to PCI [28] and then, if these data are confirmed, they could overcome these issues. Our study has some important limitations: first, it is a retrospective analysis and is therefore subject to the limitations of such analyses.…”
Section: Discussionmentioning
confidence: 99%
“…This finding may be due in part to the more critical hemodynamic conditions of these patients that are associated, mainly in cardiogenic shock, with a significant reduction of the absorption of drugs from the intestine [27], in part to the difficulty to give them the needed antiplatelet therapy, mandatory after stent implantation. New intravenous antiplatelet drugs seem promising in reducing thrombotic events related to PCI [28] and then, if these data are confirmed, they could overcome these issues. Our study has some important limitations: first, it is a retrospective analysis and is therefore subject to the limitations of such analyses.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of data supporting the feasibility of the use of cangrelor in patients undergoing PCI in need of antiplatelet therapy, cangrelor's phase III programme, two parallel CHAMPION studies (Cangrelor versus standard tHerapy to Achieve optimal Management of Platelet InhibitiON) were initiated, the CHAMPION-PCI and CHAMPION-PLATFORM studies (Table 1) [51,52]. Despite its promise, the results of both studies failed to demonstrate that cangrelor was superior to clopidogrel in terms of the primary composite endpoints at both 48 hours and at 30 days [51,52].…”
Section: Phase IIImentioning
confidence: 99%
“…Despite its promise, the results of both studies failed to demonstrate that cangrelor was superior to clopidogrel in terms of the primary composite endpoints at both 48 hours and at 30 days [51,52]. Discouraging trends in results led to premature termination of both studies.…”
Section: Phase IIImentioning
confidence: 99%
See 1 more Smart Citation
“…Cangrelor, the only intravenously administered P2Y12 inhibitor, is characterized by rapid onset and offset, with platelets regaining normal reactivity within 30 to 60 minutes of cessation,3 making it an attractive treatment for patients undergoing procedures. Trials examining its routine use compared with clopidogrel showed that cangrelor improved outcomes when used during PCI, and reduced the risk of stent thrombosis and death among patients who received it periprocedurally 10, 11…”
Section: Introductionmentioning
confidence: 99%